PENYULUHAN MENGENAI ASPEK-ASPEK HUKUM KEGIATAN USAHA LEMBAGA PERKREDITAN DESA (LPD) DI DESA SINGAKERTA UBUD KABUPATEN GIANYAR - Yogantara, P.; Murni, R.A.R; Sumadi, P.S.; Rudy, D.G.; Westra, I.K.; Sarjana, I. M.; -, Marwanto; Priyanto, I. M. D.; Utami, P. D. Y.; Mayasari, I D. A. D. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i02.p09, 2022)
This activity of community dedication aims to provide understanding for Rural Credit Institution (Lembaga Perkreditan Desa) managers regarding legal aspects in carrying out business activities, especially in providing credit to the community, so that they can realize good management Rural Credit Institution (Lembaga Perkreditan Desa)  and are able to solve legal problems faced. The method used in carrying out this activity is the method of counseling or lectures followed by in-depth discussion and question and answer. The results of this legal counseling activity showed that this activity was quite successful, as can be seen from the presence of all management and staff of Rural Credit Institution (Lembaga Perkreditan Desa) of Singakerta Village in this legal counseling activity. The management and staff in general still do not understand the legal aspects of Rural Credit Institution business activities, especially regarding the legal aspects of guarantees in providing credit to the community. Legal problems that are generally faced by Rural Credit Institution (Lembaga Perkreditan Desa) in Singakerta Village are problems related to the settlement of bad loans, procedures for execution of guarantees, and legal aspects of public saving. This activity is carried out with in-depth and detailed discussion and question and answer so that the objectives of this activity can be achieved properly. Keywords: Counseling, legal aspects, Village Credit Institutions (LPD)